Pengaruh ASEAN Disability Forum Terhadap Pengembangan Ekonomi Penyandang Disabilitas di Indonesia - Demeiati Nur Kusumaningrum; Olivia Afina; Riska Amalia Agustin; Mega Herwiandini (Insignia: Journal of International Relations, 2017)
AbstractDisabilities is a person who has a physical defect that affects their activity in society. Their problems like as discrimination, social imbalance, less of infrastructur, and the lack of employment opportunities is the assignment of the government to completion of that injustice. Indonesian became one of the country that haven’t be able to solve the problems of disability. It’s also be a serious discussion in ASEAN. So, in 2011 the ASEAN leaders agreed on the establishment of ASEAN Disability Forum as a container to accommodate the aspirations of ther disabilities in order to their justice. ASEAN Disability Forum expected to solve the problems of disability in other ASEAN countries, especially in Indonesia. The main problem is expected to be resolved is employment opportunities for the disabled so as to improve their lives.Keywords: Disabilities, ASEAN Disabiliy Forum, IndonesianAbstrakPenyandang disabilitas merupakan seseorang yang memiliki keterbatasan fisik sehingga mempengaruhi segala aktivitasnya di masyarakat. Permasalahan mereka seperti diskriminasi, ketimpangan sosial, keterbatasan infrastruktur, serta minim nya peluang kerja menjadi tugas pemerintah dalam penyelesaian ketidakadilan tersebut. Indonesia menjadi salah satu negara yang masih belum mampu menangani permasalahan penyandang disabilitas. Hal ini juga menjadi pembahasan serius di ASEAN. Sehingga, pada tahun 2011 para pemimpin ASEAN menyepakati dibentuknya ASEAN Disability Forum sebagai bentuk wadah untuk menampung aspirasi para disabilitas agar memperoleh keadilan mereka. ASEAN Disability Forum diharapkan mampu menyelesaikan permasalahan para disabilitas di negara ASEAN, terutama di Indonesia. Permasalahan utama yang diharapkan bisa terselesaikan yaitu kesempatan kerja bagi para penyandang disabilitas sehingga mampu meningkatan taraf hidup mereka.Kata-kata Kunci : Disabilitas, ASEAN Disability Forum, Indonesia